Biomimetic Materials in Restorative Dentistry and Endodontics – A Review - Monika Mohanty; Shashirekha Govind; Rini Behera (Institute of Medico-legal Publications Pvt Ltd, 2021)
In 1950, while researching the nerves in a squid, Otto Schmitt coined the word “Biomimetics” It meansimitating life, literally. To seek to mimic or reproduce it artificially to preserve the same esthetics or work is thestudy of natural structural processes. Since tooth structure has no natural means for restoration, biomimeticmethods can be implied to restore the teeth mechanically to its normal function and esthetics. There are twothings of biomimetic dentistry. First, the damaged or absent dental tissue is replaced, leading to completerestoration to the tooth of function and aesthetics. And the substance used will regenerate the damaged dentaltissue, replicate and imitate it. The bio-compliant and Physico-chemical products of biomimetic materialhave the benefits of improved biocompatibility, sealing ability, high strength, antibacterial properties andare used to preserve long term esthetic and restoring techniques. Recent biomimetic technologies haveestablished the potential to transcend various considerable drawbacks of technologies of a previous age. Thisstudy would seek to provide a clearer explanation for biomimetic materials ‘relative role in the sense of pastand current dental materials.